2018
DOI: 10.1177/1945892418815044
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Radiologic Findings in Failed Dacryocystorhinostomy: Teaching Pearls for Success

Abstract: Background Although several studies have commented on causes of dacryocystorhinostomy (DCR) failure, detailed description of anatomical findings in such cases remains insufficient. Objective Our objective was primarily to analyze radiologic, endoscopic, and intraoperative findings in patients presenting with failed DCR and secondarily to assess the outcome of revision endoscopic DCR (endo-DCR) carried out at our institution. Methods Twenty-four failed DCRs presenting to our tertiary care center were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…We found that 12.0% (179/1489) of the affected eyes have C1 ethmoid, 59.0% (878/1489) have C2, and 29.0% (432/1489) have C3. Our findings were in accordance with other published reports [7][8][9]17,[20][21] . During routine En-DCR, osteotomy is initiated at the lacrimomaxillary suture and then carried forward into the nasal fossa until the lacrimal sac is exposed [1][2]11,15] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that 12.0% (179/1489) of the affected eyes have C1 ethmoid, 59.0% (878/1489) have C2, and 29.0% (432/1489) have C3. Our findings were in accordance with other published reports [7][8][9]17,[20][21] . During routine En-DCR, osteotomy is initiated at the lacrimomaxillary suture and then carried forward into the nasal fossa until the lacrimal sac is exposed [1][2]11,15] .…”
Section: Discussionsupporting
confidence: 94%
“…These sinuses often project past the ethmoid bone suture and into the lacrimal and maxillary bones of the lacrimal sac fossa. Therefore, understanding the physical interaction between the anterior ethmoid air cells and the lacrimal sac fossa is essential for DCR [7][8][9]11] . Unfortunately, an ethmoid-cell entry may present a blind cul-de-sac and can lead to surgical failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light reflex that was observed intranasally determines the target of the lacrimal sac. Either a 20-/23-gauge vitreoretinal fiberoptic endoilluminator or a lighted lacrimal stent could be inserted and this procedure could be conducted at the beginning of endo-DCR before the mucosa is incised [21][22][23]. However, in our experience, the light could be insufficient in the case of a very thick frontal process of the maxilla or hypertrophied nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Wise surgeons realize that we learn much more from our failures than our successes. Herzallah and colleagues 4 reported a detailed analysis of their series of 24 patients who had previously failed dacryocystorhinostomy. Radiographic analysis demonstrated the most common findings being an incompletely removed uncinate process leading to retained lacrimal bone over the sac as well as limited removal of the ascending process of the maxilla and agger nasi leading to a poorly placed or suboptimaly sized rhinostoma.…”
mentioning
confidence: 99%